Effects Of Using Audio (hearing) And Visual (sight) Techniques To The Teacher Self Efficacy In Teaching Ibadah: Pilot Study Among Excellent Teachers Of Islamic Education. Tinta Artikulasi Membina Ummah (tamu) - Noornajihan Ja‘afar; Robiatul Adawiyah Mohd @ Amat; Nurul Asiah Fasehah Muhamad; Hishomudin Ahmad; Norzulaili Mohd Ghazali; Nur Hanani Hussin; Nurul Nabila Ahmad Ruslan; Ikmal Hafiz Jamal; Juliyana Junaidi (PIMM Expert Sdn. Bhd., 2024)
Non-indexed Publication